A New Look at the Electroweak Interactions of Hadrons - Chia, Swee Ping (AIP Publishing, 2008)
The Standard Model (SM) of elementary particles, in terms of quarks and leptons, is in good agreement with experimental observations. But unlike the leptons, quarks do not exist in free states. They are instead tightly bound in hadrons, which consist of mesons and baryons, which are themselves quark-antiquark states and 3-quark states respectively. Processes involving hadrons are however, complicated. Quarks are subjected to strong forces which are described by quantum chromodynamics (QCD). Because quarks are tightly bound in hadrons by QCD forces, calculations obtained at the quark level cannot be extended, in a straight-forward way, to physical processes involving hadrons. But quarks tightly bound inside hadrons behave like free particles. In this paper we take advantage of this property and formulate a simple model for the effective description of the electroweak interactions of quarks bound in hadrons. We assume that quarks in hadrons are dressed because of the QCD effects, and are represented by their effective dressed masses in electroweak processes. We apply this simple model to the semi-leptonic decays of hadrons, which are described, at the quark level, by the tree level weak interaction. The experiment decay rates are utilized to obtain estimates for the dressed quark masses in hadrons. A reasonable set of values for such dressed masses are obtained.